2016
DOI: 10.1111/jsr.12417
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a single‐channel EEG sleep study to polysomnography

Abstract: Summary An accurate home sleep study to assess electroencephalography (EEG)-based sleep stages and EEG power would be advantageous for both clinical and research purposes, such as for longitudinal studies measuring changes in sleep stages over time. The purpose of this study was to compare sleep scoring of a single-channel EEG recorded simultaneously on the forehead against attended polysomnography. Participants were recruited from both a clinical sleep center and a longitudinal research study investigating co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
117
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(128 citation statements)
references
References 21 publications
9
117
1
1
Order By: Relevance
“…These studies all showed promising results, but involved a limited number of participants and also restricted electrode positioning. Other user-mounted systems have been developed specifically for sleep (Levendowski et al, 2017;Younes, Soiferman, Thompson, & Giannouli, 2017Lucey et al, 2016Shambroom et al, 2012;Werth and Borbely, 1995), but these systems all require electrodes to be placed in highly visible locations. Ear-centered EEG solutions come with the benefit of being sufficiently discrete and therefore acceptable to users also for routine applications during the daytime.…”
Section: Introductionmentioning
confidence: 99%
“…These studies all showed promising results, but involved a limited number of participants and also restricted electrode positioning. Other user-mounted systems have been developed specifically for sleep (Levendowski et al, 2017;Younes, Soiferman, Thompson, & Giannouli, 2017Lucey et al, 2016Shambroom et al, 2012;Werth and Borbely, 1995), but these systems all require electrodes to be placed in highly visible locations. Ear-centered EEG solutions come with the benefit of being sufficiently discrete and therefore acceptable to users also for routine applications during the daytime.…”
Section: Introductionmentioning
confidence: 99%
“…18 A second study evaluated the agreement with PSG in a group that included elderly control patients for an Alzheimer disease investigation. 19 The first part of the current study was intended to demonstrate the validity of sleep biomarkers by first evaluating the accuracy based on the agreement in the autostaging from frontopolar sites to simultaneously acquired PSG in a group of patients mainly referred for probable obstructive sleep apnea. In the second part of this study, we evaluated the night-to-night consistency of sleep biomarkers identified by this device in a clinical population of insomnia patients vulnerable to a firstnight effect.…”
Section: Scientific Investigationsmentioning
confidence: 99%
“…After rejection of periods when the absolute amplitude is ≥ 500 µV, the signals were notch filtered, and then infinite impulse response band pass-filtered to obtain 16 Hz samples of the power values for delta (1-3.5 Hz), Delta C (delta power corrected for ocular activity), theta (4-6.5 Hz), alpha (8-12 Hz), sigma (12)(13)(14)(15)(16), beta (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), and EMG bands ( > 40 Hz with a 80 Hz, 3 dB rolloff). A second set of power values was obtained after application of a 0.75-Hz highpass filter.…”
Section: Softwarementioning
confidence: 99%
“…Previous small‐sample‐size studies have evaluated automated scoring software using single‐channel EEG data (Fietze et al., ; Fraiwan, Lweesy, Khasawneh, Wenz, & Dickhaus, ; Garcia‐Molina et al., ; Lucey et al., ; Su, Luo, Hong, Nagurka, & Yen, ; Zhang & Wu, ; Zhu, Li, & Wen, ). In 15 healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…Previous small-sample-size studies have evaluated automated scoring software using single-channel EEG data (Fietze et al, 2015;Fraiwan, Lweesy, Khasawneh, Wenz, & Dickhaus, 2012;Garcia-Molina et al, 2015;Lucey et al, 2016;Su, Luo, Hong, Nagurka, & Yen, 2015;Zhang & Wu, 2018;Zhu, Li, & Wen, 2014 patients. However, the agreement was slightly lower for the singlelead EEG by itself than when EOG and EMG data were added to the analysis (Fietze et al, 2015).…”
Section: Ahi Calculationmentioning
confidence: 99%